Strategy to accelerate COVID-19 vaccination coverage - Nildawati, Nildawati; Ilhamsyah, Ilhamsyah (Universitas Muhammadiyah Purwokerto, 2022)
Vaccination is carried out as an integrated effort to maximize the target of achieving vaccination to reduce mortality, break the chain and achieve herd immunity. Herd immunity can be achieved if the vaccination coverage is 60% -70%. However, until now, there have been many challenges in increasing the coverage of this vaccination. The Government has made various efforts to maximize the achievement of vaccination, but until now, the vaccination has yet to reach the target of 80%. Various factors and obstacles cause this, so a concrete strategy is needed to overcome them. In addition to regulations from the Government, a socio-cultural approach strategy is also needed considering that Indonesia is a country with various ethnicities and beliefs, so perceptions and acceptance of vaccination are also different for each region and society.